Creativity in parenting: the prophetic tradition as an exemplary guide in teaching virtues to children for a sustainable future - Zejno, Bukuri (2020)
Parenting is one of the most impactful aspects of life that requires and deserves substantial investments for a sustainable future. Since the way we parent our children determines to a great extent the way they view the world and their role in it, this paper will look at how creativity can be utilized and engaged to teach them valuable virtues, which can shape them and help them shape their own future, including the Hereafter. This study uses an analytical method to refer to selected Prophetic traditions and offers a number of creative approaches that can be used in parenting, such as the analogy, looking at things from a fresh perspective, connection before correction, alternative solutions for attention and quality time, and ways of expressing unconditional love and affection. The outcome of this paper will contribute to the revival of the Prophet (p.b.u.h.)’s creative methods, which are applied to parenting and serve as an exemplary guide for teaching virtues to children.